ANALYSIS ON SPROCKET AND CHAIN RING OF SCRAPER CONVEYOR UNDER PERFORMANCES OF CHAIN JAMMED - XIE Miao; YAN JiangLong; MAO Jun; DONG XianRui; LI Cui (Jixie qiangdu)
The chain scraper conveyor is the most important material conveying equipment in the fully mechanized working face,and the sprocket and the chain ring is the core part of the conveyor system,the meshing problem of the sprocket and the chain ring is the most prominent problem of the transmission system. In order to research the rules of the sprocket contact force under the chain condition,first of all from the chain ring and sprocket meshing process carries on the theoretical analysis,and has carried on the analysis to his contact force changes. Then established the visual prototyping model based on the MSC. ADAMS and analyzed the touch dynamics quality between sprocket and chink hoop when the scraper conveyor starts and are operated for a long time. The change law of the contact resultant force tangential force and normal force when the sprocket and the chain ring are engaging,and the maximum engaging force and the corresponding position are analyzed. Finally we analyzed the engaging force when the sprocket and chain ring during the engaging progress based on software of workbench,and got the maximum engaging force and corresponding position,which provides the theoretical basis for the optimization design of the scraper conveyor sprocket and the chain ring.